A systematic literature review of optimal placement of fast charging station - Jimmy Trio Putra; M. Isnaeni Bambang Setyonegoro; Taco Niet; Sarjiya (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
Electric vehicles (EV) have increased in the last few decades due to their ability to reduce greenhouse gas emissions (GHG). Support for the electrification of the transportation sector has encouraged researchers to investigate the optimal placement of fast charging stations (FCS). In this study, we conducted a systematic literature review of 84 primary studies between 2019 and 2024 by identifying objective function and solution techniques, uncertainty, stakeholders, and network classification. We identified the objective functions most commonly used by authors related to technical and cost-solving problems using techniques: conventional (41.7%), metaheuristic (33.3%), hybrid (22.6%), and other (2.4%). Several researchers have also considered various uncertainty parameters from EV, FCS demand, and distributed generation (DG) power output with the most popular probabilistic method to solve problems. Furthermore, the role of stakeholders and network classification is also reviewed in this article. Our study contributes to the field by providing a comprehensive overview of the most significant journals and highlighting future research on the optimal placement of FCS. Future work must focus on improving parameters, models, methods, and using real data from various factors related to FCS demand.